2022
DOI: 10.1155/2022/8242210
|View full text |Cite
|
Sign up to set email alerts
|

Strength Level of Professional Elite Soccer Players after the COVID-19 Lockdown Period: A Retrospective Double-Arm Cohort Study

Abstract: Background. It is well known that periods of inactivity generate a loss of muscle strength, a fundamental component of sports performance in soccer. However, little information is available on the decrease in strength levels in professional soccer players after the quarantine lockdown that occurred during the COVID-19 pandemic. Aim. To compare the isokinetic peak torque profiles of professional soccer players from different teams before and after the quarantine period generated by COVID-19. Methods. A retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…The 29 studies selected for systematic review [ 8 , 9 , 10 , 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and the quality of all of the studies analyzed are presented in Table 1 . The details of these studies are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 29 studies selected for systematic review [ 8 , 9 , 10 , 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and the quality of all of the studies analyzed are presented in Table 1 . The details of these studies are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the motivation of exclusion was as follows: the number of subjects per group was not clear [ 24 ]; the data of O2peak was reported in other measurement units (meters) [ 31 ]; and no access to data in mean and standard deviation (even after email request) [ 43 , 45 , 46 ]. A total of 24 studies [ 8 , 9 , 10 , 13 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 47 ] and 447 athletes were included in this meta-analysis. This study resulted in six forest plots.…”
Section: Resultsmentioning
confidence: 99%
“…Grazioli et al ( 2020 ) also reported no significant changes in hamstring eccentric strength in male professional soccer players after 63 days of home training compared to tests after the traditional off-season period. Another study found that in professional soccer players, in whom home training was controlled by video training, no changes in isokinetic peak torque were noted in contrast to the group of soccer players who were not controlled (Scoz et al, 2022 ). In contrast, another study showed reduced eccentric hamstring strength in soccer players in a 7-week home training period despite a training program that included strength-based activities (Moreno-Pérez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Positional groupings were goalkeepers (G), defenders (D), sidebacks (S), midfielders (M) and forwards (F). Dominant leg was defined as their preferred kicking leg for a penalty kick [4,[32][33][34]]. Anthropometric information was recorded by team's medical staff before players completed a standardized warm-up on the isokinetic machine to minimize error.…”
Section: Methodsmentioning
confidence: 99%
“…However, some athletes employ personal trainers or follow their team's coach regular training regime. A recent study of our group [34], found that this strategy was used during COVID-19 lockdown regime by some teams with different results.…”
Section: Limitationsmentioning
confidence: 99%